The Development of Kahoot-Based Learning Media Cooperative Learning to Improve Learning Motivation - Ilmudinulloh, Rafiud; Bustomi, Ahmad; Pratiwi, Widya Rizky (Institut Agama Islam Negeri Kediri, 2024)
This study aims to develop learning media based on Kahoot! in cooperative learning to increase the learning motivation of Islamic Religious Education students. The 4D research design, which consisted of defining, designing, developing, and disseminating, was chosen to produce Kahoot! based media. Data were collected using observation sheets and questionnaires. The data was then analyzed using descriptive statistics. It was concluded that learning media based on Kahoot! suitable for use in cooperative learning and can increase student learning motivation. This is evidenced by the results of the media expert test with very good criteria or 93%, the material expert test with good criteria, or 88%, the field test with very good criteria, or 95%, and the learning motivation test with very high and effective criteria. Media Kahoot! as a quiz helps the implementation of cooperative learning with design and game elements relevant to the main principles of cooperative learning such as collaboration, student engagement, active learning, and appreciation. The availability of supporting facilities such as loudspeakers, projector screens, and the Internet has an important role in using Kahoot! media. because it is quite influential on the students’ psychological atmosphere and the fluency of cooperative learning.